Pelatihan Pembuatan Peta Kelurahan Se-Kecamatan Galang Kota Batam - Sudra Irawan; Oktavianto Gustin; Arif Roziqin; Rizki Widi Pratama; Luthfiya Ratna Sari; Nanik Lestari; Fajar Muliana; Vina Selvia Dwiyanti; Muslimin Muslimin; Gregorius Harry Saktian Sinaga; Agus Fatulloh; Mir'atul Khusna Mufida; Afdhol Dzikri; Evaliata Sembiring; Selly Artaty Zega (Pusat P2M Politeknik Negeri Batam, 2019)
Galang, with Sembulang as its capital city, is located in Batam, Riau Islands. Based on the results of the field survey on August 21st-23rd 2018 conducted in the Galang Administration Office and the Sembulang Administration Office, it was found that there was no subdistrict and village map which is up to the cartographic rules, which could pose a problem. In fact, there were no villages in Galang, other than Sembulang, which possessed a village map. The awareness from the community regarding the importance of charting a village map was still relatively low, resulting in many errors regarding cartometric boundaries. In addition, the community and the village officials’ understanding regarding the use of a map as a basis to manage space in developing the region was still also inadequate. To overcome this problem and fulfill the need of the people, the Galang Subdistrict Head approved this community service activity. The program aims to deliver a training on charting maps of villages in Sembulang, Batam, which consists of three main activities: instruction on the use of handheld GPS, delineation of Google Earth imagery, and documentation of geospatial information. The training (in the form of Bimtek) was carried out on Tuesday, August 6th, 2019, attended by 39 participants, comprising the Galang sub-district officials as well as the head, secretary, and officials of each village. The activities started from the delivery of topics regarding the scope of geospatial information and the use of map, followed by training in the use of handheld GPS to record spatial data such as public facilities and tourist attractions, and concluded by training in plotting village maps using the Argish software.